Are carbon pricing policies on a path to failure in resource-dependent economies? A willingness-to-pay case study of Canada. (March 2022) - Benjamin, Emmanuel O.; Hall, Daniel; Sauer, Johannes; Buchenrieder, Gertrud
Abstract: There are limited studies on specific factors that affect willingness-to-pay (WTP) and public concerns on spending of pollution pricing in democratic economies that are carbon dependent. In light of the discourse on global pollution pricing, this study explores the complex influence of political-economic, attitudinal, and socio-demographic factors on carbon pricing, by estimating the WTP in a carbon resource-dependent economy such as Canada and the preferred revenue earmarking of Canadians. An online survey of 600 Canadian households was conducted using the random device engagement (RDE) approach. This study uses a contingent valuation method (CVM) and payment card (P.C.) to estimate the household WTP for carbon pricing on direct energy expenditure and an ordered logistic regression model for odds ratio estimates. The estimated annual WTP ranges between CAD$ 84 to CAD$ 230 in 2019 (CAD$ 1 = US$ 0.7538). This implies an acceptable increment of 1.5%–2.5% (CAD$ 157 to CAD$ 259) to the average yearly household energy expenditures. This study suggests that Canadians appear to be supportive of redistributing carbon price revenues and investing in clean energy technology. Canadian government needs to address public concerns surrounding political-economic factors, specifically the energy cost implication for vulnerable households in order to achieve emission reduction targets. Research Highlights: Investigate determinants of Canadian WTP for carbon pricing on household energy costs. The annual WTP ranges between CAD $83.81 (US$63) to CAD $230.40 (US$174) in 2019. Higher WTP, driven by education, climate policy beliefs and perceived fairness. Canadians prefer investment and redistribution of carbon price revenue as earmarking.